ANALYSIS OF PREFERENCES ON PURCHASE INTENTION OF THE COMMUNITY IN THE TIKTOK SHOP APPLICATION BASED ON E-WOM, ADVERTISING, AND LIVE ONLINE IN GENERATION Y - Ratri Purwaningtyas; Ismayanti Rahmi; Rahmayanti (International Journal Management and Economic, 2026)
Generation Y is a demographic group born between 1981 and 1996. This generation grew up during the digital era and rapid technological development, making them proficient in using the internet, social media, and digital devices. Generation Y is also known for their tendency to care about social and environmental issues as well as seeking a balance between work and personal life. This study will analyze the influence of three variables, namely e-WOM, advertising, and live online, on the purchase intention of Generation Y consumers in the TikTok Shop application. A quantitative method was employed by distributing samples to 97 TikTok Shop users born between 1981 and 1996, determined using the Lemeshow formula. The data analysis process began with validity testing to determine data validity, followed by reliability testing, normality testing, heteroscedasticity testing, multicollinearity testing, partial hypothesis testing (t-test), and simultaneous hypothesis testing (F-test). Subsequently, the partial and simultaneous effects on the independent and dependent variables were measured. The results showed that e-WOM, advertising, and live online partially and simultaneously have a significant and positive effect on the purchase intention of Generation Y consumers on TikTok.